IMPLEMENTASI KARAKTER RELIGIUS DALAM MENJALANKAN IBADAH MAHDHAH MELALUI KEGIATAN PENGAJIAN MAJLIS TA’LIM - Erizon, Erizon; Fadhlan, Muhammad (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2023)
The background of the problem in this research is that many members who neglect the prayer cause the active of participation in following majlis ta’lim not followed by obedience in performing shalat, The purpose of this research is to find out perceptions of mothers of Majlis ta'lim Nurul Huda Desa Lawang Agung about prayer through following the teaching of majlis ta'lim Nurul Huda activity at Lawang Agung Village, Pondok Tinggi Subdistrict, Sungai Penuh city and to know the forms of teaching activities, and to know the supporting factors and the obstacle factors of Majlis Ta’lim on the implementation of devout religious characters in performing ibadah mahdhah, especially in shalat. The results of this research found that the understanding of housewives about shalat there are four criteria, there are: the mothers know and understand about shalat, able to Apply their Understanding in Practice, able to interpret the value of shalat in the form of deeds, and able to actualize the value of Salat in the form of Behavior and Action. Based on the results of the research above can be concluded that the the implementation of obedient religious character of Majlis Ta’lim members through majlis ta’lim teaching activities can be used as a momentum to improve the faithful and devotion to Allah SWT especially in performing shalat.